Characteristics of 2024/3003 aluminium alloys bimetal prepared by direct chill casting. (November 2014) - Liu, N.; Song, X. Y.; Jie, J. C.; Fu, Y.; Li, T. J.
<x content-type="archive" xml:space="preserve">Abstract</x> A direct chill semicontinuous casting process to prepare 2024/3003 clad slab has been developed in the present study. Microstructure, solute distribution and bonding strength of the interfacial regions of clad slab were investigated by methods of metallographic examination, electron probe microanalysis and tensile tests. The results show that an excellent metallurgical bonding between the two different alloys can be achieved with optimal parameters. The 3003 alloy, which was poured into the mould earlier, serves as the substrate of heterogeneous nucleation of 2024 alloy. The Cu and Mg atoms diffuse from the 2024 side into the matrix of 3003 side, while Mn atoms diffuse in the opposite direction. The mean tensile strength of clad slab is 118 MPa, and the strength of the interface is higher than that of 3003 alloy.